Indonesia : Report on Observance of Standards and Codes; Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The abstract summarizes the Report on Observance of Standards and Codes and Fiscal Transparency Module of Indonesia. It highlights that a strategy for improving transparency and strengthening fiscal management should be included in the reform program, including implementing recent changes in legislation. It also discusses the clarity of roles and responsibilities, open budget preparation, executing, and reporting. The Executive Board stressed the need to deepen reforms in the central government budgetary sector and to have comprehensive general government transparency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet